Professional trumpet players on double-tonguing technique / Muhammad Fakrur Razi Azian - Azian, Muhammad Fakrur Razi (2020)
The lack of practice and not having enough knowledge on how to properly execute the techniques of trumpet playing are one of the main problems that trumpet players go through in the phase of becoming an astounding musician. Trumpet players must put a lot of efforts and give a full commitment in wanting to achieve a very bright future as a professional trumpet player. This research aim to study on how to develop double-tonguing technique, what are the issues that trumpet players go through while executing double-tonguing and how to overcome those issues. This research is based on interview conducted with 5 professional trumpet players with different music background. The interview consists of what was the respondent’s experience as a trumpet player, what are their daily practice routines and of course questions for the main focus on double-tonguing technique. The research suggested that successful double-tonguing technique can be achieve by giving a full commitment in terms of continuous practicing and patience. This research will eventually give a proper guidance for new trumpet players to master the technique.